Strength development and durability requirement in recycled aggregate concrete: effect of drying and post curing - Chauhan B.L.; Singh G.J.; Kumar A.; Kumar R. (My University, 2025)
Present research critically investigates drying sensitivity and cement hydration resumption in recycled aggregate concrete (RAC). To determine minimum post-curing time for optimum strength resumption in RAC, a curing ratio (δ) is introduced. Curing ratio is defined as the ratio between post-curing duration and delay time before curing. Drying sensitivity of RAC is observed significantly lower than NAC. The maximum strength loss under drying conditions is 25.9% in RAC (OPC) and 23.2% in RAC (PPC). Strength criteria determine the curing ratios of RAC (OPC) and RAC (PPC) as 2.22 and 0.30. The maximum delay time for RAC (OPC) and RAC (PPC) is determined at 8 days and 21 days with a minimum post-curing for 17.76 and 6.63 days. The longest allowable delay produces ion penetration less than 1000 Coulombs, resistivity greater than 208 ohm-m, superior structural integrity and internal compactness, and sorptivity comparable to RACs cured after a shorter delay. © 2024 Informa UK Limited, trading as Taylor & Francis Group.